Exercise and Oxidative Stress Biomarkers among Adult with Cancer: A Systematic Review. (18th February 2022) - Longobucco, Yari; Masini, Alice; Marini, Sofia; Barone, Giuseppe; Fimognari, Carmela; Bragonzoni, Laura; Dallolio, Laura; Maffei, Francesca
Abstract : Evidence shows that exercise can have a favourable effect in cancer patients. The exercise's clinical benefits are likely to concern multiple interrelated biological pathways, among which oxidative stress plays a key role. Regular training can induce an adaptive response that strengthens the antioxidative status of the body. To formulate public health recommendations regarding the optimal exercise prescription for cancer patients, a detailed understanding is needed regarding the effect of exercise on variables linked to oxidative stress and antioxidant status of patients. The goal of this systematic review, based on PRISMA, was to explore and critically analyse the evidence regarding the efficacy of exercise on oxidative stress biomarkers among people with cancer. Study search was conducted in the following databases: PubMed, Cochrane, CINAHL, Embase, PEDro, and SPORTDiscus. The studies' quality was assessed with the Cochrane risk-of-bias tool and STROBE scale. After identification and screening steps, 10 articles were included. The findings provide an encouraging picture of exercise, including resistance training and aerobic activities, in people with cancer. The exercise improved the indicators of the total antioxidant capacity, increased the antioxidant enzymes' activity, or reduced the biomarkers of oxidative damage in various forms of cancer such as breast, lung, head, and neck. Regarding oxidative DNA damage, the role of exercise intervention has been difficult to assess. The heterogeneity of study design and the plethora of biomarkers measured hampered the comparison of the articles. This limited the possibility of establishing a comprehensive conclusion on the sensitivity of biomarkers to estimate the exercise's benefits. Further high-quality studies are required to provide data regarding oxidative stress biomarkers responding to exercise. This information will be useful to assess the efficacy of exercise in people with cancer and support the appropriate prescription of exercise in anticancer strategy.